2014
DOI: 10.1126/science.1250515
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Between Science and Environmental Education

Abstract: Citizen science and concerns about sustainability can catalyze much-needed synergy between environmental education and science education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
189
0
32

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(221 citation statements)
references
References 16 publications
0
189
0
32
Order By: Relevance
“…Further enhancement through social media, could therefore promote the new types of collaboration and collective action vital for the transition to sustainable food security, driving behaviour change to re-shape the agri-food ecosystem. Innovative programmes bringing together science education and environmental education can help establish the conditions and learning processes needed for the cultural shift towards food security (Wals et al, 2014). Recent research has shown how people are willing to sacrifice personal gain to preserve resources for future generations when they are assured that others will do likewise, decisions being made by majority voting effectively constraining selfish minorities (Hauser et al, 2014).…”
Section: Share Data Information and Methodology Widely And Freely Ammentioning
confidence: 99%
“…Further enhancement through social media, could therefore promote the new types of collaboration and collective action vital for the transition to sustainable food security, driving behaviour change to re-shape the agri-food ecosystem. Innovative programmes bringing together science education and environmental education can help establish the conditions and learning processes needed for the cultural shift towards food security (Wals et al, 2014). Recent research has shown how people are willing to sacrifice personal gain to preserve resources for future generations when they are assured that others will do likewise, decisions being made by majority voting effectively constraining selfish minorities (Hauser et al, 2014).…”
Section: Share Data Information and Methodology Widely And Freely Ammentioning
confidence: 99%
“…Transformative learning then emerges from dialogue between groups with diverse sets of values and worldviews, in which each group is brought to refl ect on and creatively re-consider their own ways of thinking and doing ( Lotz-Sisitka et al, 2015 ) (see Section 1.4). There is an interesting convergence in the literatures on procedural requisites for transformative sustainability science and social learning, or transformative social learning for sustainability ( Peters & Wals, 2013 ;Wals et al, 2014). Understanding diverse facets of challenges from distinct perspectives of different experts and stakeholders who engage in transformative social learning from each other is deemed necessary to better understand complexity Newell & Doll, 2015;Dyball & Newell, 2015 ).…”
Section: What Knowledge For Sustainability?mentioning
confidence: 99%
“…Platforms for analytic deliberation to deal with value confl icts are required (Dietz et al, 2003;Ison et al, 2007 ). Social learning focuses on the relation of learning across different scales of social organization: individual, group, organizational, or societal ( Medema et al, 2014 ;Wals et al, 2014 ). Building on this research, learning is conceived of in this book as a process of developing enriched understandings and repertoires of action on complex problems as a result of open and iterative cycles of experimentation, observation, analysis, and judgment of results.…”
Section: Sustainability Science As a Transformative Social Learning Pmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of different ways in which citizen science [8,9] can contribute to conservation at landscape scales. On the simplest level, it is common for amateur scientists or people from local communities to contribute to databases on the flora and fauna of particular areas.…”
Section: Introductionmentioning
confidence: 99%